2007
DOI: 10.1080/09593980701593771
|View full text |Cite
|
Sign up to set email alerts
|

Doppler insonation of vertebral artery blood flow changes associated with cervical spine rotation: Implications for manual therapists

Abstract: The controversy related to changes in vertebral artery (VA) blood flow associated with rotation of the cervical spine and the implications for professional practice is still of concern to manual therapists. The aim of this review of the literature is, first, to assess current evidence of altered VA blood flow following cervical spine rotation in persons with and without signs and symptoms of vertebrobasilar ischemia/insufficiency (VBI). Second, any reported, related alterations in blood flow that may have cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 68 publications
0
24
0
2
Order By: Relevance
“…Two MOs commented that they no longer used positional tests involving extension, but continued to use rotation. This finding is notable as there is conflicting evidence in the literature from Doppler ultrasound studies regarding the validity of these tests; 28 however, evidence suggests that rotation does influence blood flow in the vertebral artery in some individuals. 12,26 There are also published reports of (false) negative tests despite known dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Two MOs commented that they no longer used positional tests involving extension, but continued to use rotation. This finding is notable as there is conflicting evidence in the literature from Doppler ultrasound studies regarding the validity of these tests; 28 however, evidence suggests that rotation does influence blood flow in the vertebral artery in some individuals. 12,26 There are also published reports of (false) negative tests despite known dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…Traditionally, the upper cervical spine is believed to carry a greater risk because of the tortuous course of the VA between C2 and the occiput. Most blood fl ow studies have concentrated on the C1/C2 and cervical anatomical area 25,29,30,32,[73][74][75] . Some fl ow studies have insonated the vessel as it enters the lower part of the vertebral column (the pre-transverse level) 22,[76][77][78][79][80] .…”
Section: What Is the Relative Risk Of Manipulating The Upper Cervicalmentioning
confidence: 99%
“…Some fl ow studies have insonated the vessel as it enters the lower part of the vertebral column (the pre-transverse level) 22,[76][77][78][79][80] . Few studies have measured blood fl ow in the intracranial VA 21,23,24,28 where it may be argued that VA blood fl ow related to the upper cervical spine would be a more accurate measure of fl ow change 24,32,73,74 . It has also been shown that VA atherosclerotic plaques do exist throughout the course of the VA 64 .…”
Section: What Is the Relative Risk Of Manipulating The Upper Cervicalmentioning
confidence: 99%
“…The mechanistic reasoning for measuring blood flow in relation to adverse events is principled initially in the idea of altered haemodynamics being a fundamental component of vessel pathology (Cecchi et al, 2011). Further, flow change is considered to be indicative of the sorts of mechanical stresses responsible for the type of micro-trauma in question (Mitchell, 2007). Thus blood flow measurement remains a valid procedure to understand vascular tissue stress in the VA.…”
Section: Introductionmentioning
confidence: 99%
“…Although blood flow volume is the primary measure affecting brain perfusion (Ganong, 2005), the measure of interest in this study was blood flow velocity. Changes in blood flow velocity may be used to reflect changes in volume (Aaslid et al, 1986;Newell and Aaslid, 1992;Mitchell, 2007). Blood flow velocity and volume vary proportionally (Aaslid et al, 1986;Newell and Aaslid, 1992) in part due to the low pulsatility index of the VA, and during normal laminar blood flow the VA internal diameter does not change (Mitchell, 2009).…”
Section: Introductionmentioning
confidence: 99%